2016
DOI: 10.1016/j.ihj.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ivabradine and atenolol in patients with moderate mitral stenosis in sinus rhythm

Abstract: Ivabradine or atenolol can be used for heart rate control in patients with moderate mitral stenosis in sinus rhythm. Ivabradine is not superior to atenolol for controlling heart rate or exercise capacity. Left ventricular MPI was unaffected by either of the drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This is in contrast to the earlier meta-analysis by Adviento et al [ 20 ], where ivabradine was not significantly different to beta-blocker with regards to these clinical parameters. Individually, the included studies [ 17 - 19 ] showed that ivabradine and beta-blockers were able to similarly improve these outcomes, but in our study, it appears that ivabradine is in fact better. Dhanger [ 21 ] was able to show a statistically significant improvement in exercise duration from baseline among symptomatic MS patients in sinus rhythm, when treated with ivabradine for 3 months.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…This is in contrast to the earlier meta-analysis by Adviento et al [ 20 ], where ivabradine was not significantly different to beta-blocker with regards to these clinical parameters. Individually, the included studies [ 17 - 19 ] showed that ivabradine and beta-blockers were able to similarly improve these outcomes, but in our study, it appears that ivabradine is in fact better. Dhanger [ 21 ] was able to show a statistically significant improvement in exercise duration from baseline among symptomatic MS patients in sinus rhythm, when treated with ivabradine for 3 months.…”
Section: Discussionmentioning
confidence: 47%
“…Five studies, comprising a total of 362 patients, were included in this meta-analysis. Table 1 [ 16 - 19 , 21 ] gives the summary of the study characteristics. All of the studies are small, with the largest study having 97 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies have evaluated the effects of HR reduction with ivabradine in patients with mild to moderate MS and normal sinus rhythm (Table 3). 58–64 In all studies, ivabradine showed a significant reduction in HR from baseline. Two studies showed significant benefits with ivabradine versus β‐blockers on exercise time and working capacity, respectively 58,62 .…”
Section: Resultsmentioning
confidence: 88%
“…Beta blockers are the mainstay of therapy [27], while rate-limiting calcium antagonists or digoxin provide alternatives in atrial fibrillation. For patients in sinus rhythm, ivabradine is an emerging effective alternative [28]. If medical therapy fails, then exercise stress echocardiography is useful to assess the consequences of increase demand on transmittal gradients.…”
mentioning
confidence: 99%